Increase of Graduates by the Thesis Development at Public Universities in Peru through Collaborative Motivation - et.al, Hugo Vega (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In Peru, there is a deficit of university students who manage to graduate by the thesis development modality; in the different faculties of public universities, the number of graduates for this modality is low. This research analyses the particular situation of graduates in the faculty of Systems Engineering and Computer Science of the Universidad Nacional Mayor de San Marcos from 2014, where less than 10% of the total graduates were identified, graduate by the modality of thesis support and that more than 90% graduate through various modalities that do not include making a thesis; the consequence of this is the small amount of thesis generated and therefore the low research index as well as the null publication of scientific articles by our graduates. Therefore, this research aims to increase the percentage of graduates by the thesis development modality through collaborative motivation using virtual platforms and support graduates in the publication of scientific articles. At the end of the research, more than 50% of graduates by the thesis development modality were increased; the publication of scientific articles generated by graduates through the thesis development modality based on the results of their research was also increased